Medical downgrading, self-perception of health, and psychological symptoms in the British Armed Forces. Issue 4 (23rd March 2006) - Rona, R J; Hooper, R; Greenberg, N; Jones, M; Wessely, S
Abstract : Objective: To investigate the contribution of psychological symptoms to limited employability for medical reasons in the British Armed Forces. Methods: A sample of 4500 military personnel was randomly selected to receive either a full or an abridged questionnaire. The questionnaires asked whether the participant was medically downgraded and if yes, the reason for it. The full questionnaire included the General Health Questionnaire-12 (GHQ-12), the post-traumatic stress disorder (PTSD) checklist, 15 symptoms to assess somatisation, and selected items of the quality of life SF-36 questionnaire. The abridged questionnaire included the GHQ-4, a 14 item PTSD checklist, five symptoms, and the item on self-perception of health from the SF-36. Subjects above a threshold score for GHQ, PTSD, and symptoms were considered to have psychological symptoms. Results: 12.4% of the participants were medically downgraded. The majority (70.4%) had social or work limitations. Medically downgraded personnel had higher odds ratios in comparison to non-downgraded personnel for psychological distress 1.84 (95% CI 1.43 to 2.37), PTSD 3.06 (95% CI 1.82 to 5.15), and number of symptoms 2.37 (95% CI 2.37 1.62 to 3.47). GHQ, PTSD, and symptoms scores were mainly, but not exclusively, related to chronic physical injury. Conclusions: Psychological symptoms are common among medically downgraded personnel. Although the mechanisms involved are unclear, tackling issues of psychological symptoms among these subjects could contribute to faster restitution to full employability in the Armed Forces.